Internal Efforts of Improving Spirituality of Ministry Apartment of Religion, Medan City - Siregar, Impun; Muzakkir, Muzakkir; Nur, Anwarsyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The aim of this research is to analyze the spirituality of the State Civil Apparatus at the Office of the Ministry of Religion in Medan, the researcher will link and relate the benchmarks of this research to the Indonesian Minister of Religion's program "Five Values of Work Culture". This program is the spirit of the Ministry of Religion so that work and work are more meaningful and have values that bind and inspire them. The research methodology use qualitative research. The study conducted by the State Civil Apparatus of the Ministry of Religion in Medan is an activity that has the aim of forming good, faithful, pious, and virtuous Muslims. The purpose of recitation is the same as the purpose of Da'wah, which is to go to the righteous and stay away from the evil.